2010
DOI: 10.1890/09-1162.1
|View full text |Cite
|
Sign up to set email alerts
|

General stabilizing effects of plant diversity on grassland productivity through population asynchrony and overyielding

Abstract: Abstract. Insurance effects of biodiversity can stabilize the functioning of multispecies ecosystems against environmental variability when differential species' responses lead to asynchronous population dynamics. When responses are not perfectly positively correlated, declines in some populations are compensated by increases in others, smoothing variability in ecosystem productivity. This variance reduction effect of biodiversity is analogous to the riskspreading benefits of diverse investment portfolios in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
482
11
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 472 publications
(548 citation statements)
references
References 29 publications
(43 reference statements)
32
482
11
3
Order By: Relevance
“…In these communities, we identified a larger number of negative covariances between species populations both within the same trophic level (for basal species) and across trophic levels. This mirrors recent experimental and theoretical work on the relationship between diversity and stability in competitive communities (Tilman et al, 2006;Hector et al, 2010;Loreau and de Mazancourt, 2013). In those studies diversity was found to stabilize aggregate community or ecosystem properties while simultaneously destabilizing individual species abundances.…”
Section: Discussion Complexity and Robustness To Invasionssupporting
confidence: 79%
“…In these communities, we identified a larger number of negative covariances between species populations both within the same trophic level (for basal species) and across trophic levels. This mirrors recent experimental and theoretical work on the relationship between diversity and stability in competitive communities (Tilman et al, 2006;Hector et al, 2010;Loreau and de Mazancourt, 2013). In those studies diversity was found to stabilize aggregate community or ecosystem properties while simultaneously destabilizing individual species abundances.…”
Section: Discussion Complexity and Robustness To Invasionssupporting
confidence: 79%
“…But theory and data both support greater temporal stability of a community property like total biomass at higher levels of diversity. Five syntheses have 40 summarized how diversity impacts variation of ecosystem functions through time [38][39][40][41][42] , and these have shown that total resource capture and biomass production are generally more stable in more diverse communities. The mechanisms by which diversity confers stability include overyielding, statistical averaging, and compensatory dynamics.…”
Section: There Is Mounting Evidence That Biodiversity Increases the Smentioning
confidence: 99%
“…This hypothesis has gained support from testing in several ecosystem types, especially in grasslands (Hector et al, 2010;Cardinale et al, 2011;Morin et al, 2014). In addition to species and genotype diversity (Hughes et al, 2008), the functional diversity, i.e., the presence of species and plant functional types with different physiology, morphology, resource requirements, seasonal growth patterns and life history may increase the productivity of an ecosystem (Tilman et al, 1997;Cadotte et al, 2008).…”
Section: The Role Of Functional Diversity For Peatland Carbon Sinkmentioning
confidence: 99%